Implementation of Learning Media For Building Space Based on Temple Architecture In Mathematics Subject - Fatihah, Bella Maulida; Restian , Arina; Aini, Dian Fitri Nur (FKIP - Universitas Riau, 2025)
Elementary school students often face difficulties in understanding the concept of building space due to its abstract nature. The use of concrete learning media can help students to more clearly understand the shape and characteristics of spatial shapes, especially when related to everyday life. The method used in this research is descriptive qualitative, with data collection techniques through observation, interviews, and questionnaires. The results of questionnaires given to students and educators showed that 98% of students felt it was easier to understand the material when learning media was used effectively. In addition, 92% of teachers recognized that the use of learning media increased students' active participation in class. This research is expected to be a reference to improve the quality of mathematics learning in elementary schools. Therefore, it is expected that teachers can continue to develop and utilize learning media optimally to create more effective and interesting learning.